#TITLE_ALTERNATIVE# - ANDRIANUS JUNIAR (NIM 123 04 011), EDWIN
High-resolution seismic reflection is a promising method in the future, especially for shallow prospecting. Since the near-surface geological condition is complex and the quality of data is poor, the application of this method will produce seismic data with poor quality. Geophysicists try to improve the quality of seismic stacked section by doing data processing with more carefully, more accurate, and sometimes apply special module. One of the seismic data processing module that promising better seismic stacked section image is Zero Offset Common Reflection Surface stack, where Signal to Noise ratio (S/N ratio) and the continuity of the reflector can significantly improve. This thesis discussed the application of ZO-CRS stack method for shallow subsurface target. The study is begun with constructing synthetic seismic reflection data. The program of FWM2DPSV is used to create the synthetic data. The model consists of 4 sedimentary layers, deeper layers formed anticline structures. The dimension of model is 290 m length and 115 m depth. The thickness of layers is between 10 to 40 meters. In order to simulate the seismic waveform, high frequency source with dominant frequency of 150 Hz must be applied. The synthetic data shows not only reflection events, but also converted waves. The ZO-CRS stack method then applied to the synthetic data. To show the advantages of ZO-CRS stack method, a conventional stacking method is also applied for comparison purposes. The results from seismic data processing shows that the ZO-CRS stack method have the capability to reduce the noise from the subsurface image and to increase the Signal to Noise ratio. The conclusion of this research shows that ZO-CRS stack method have better capability to produce subsurface image than conventional stacking method. Besides that, the ZO-CRS stack method produce attributes that can use for interpretation purposes.